Con el futuro que soñamos los neogranadinos: proposiciones de avance económico para una nueva realidad social (1778-1813) (2021)
This historiographical article identifies and explains the economic approaches outlined by prominent enlightened Creoles from the late 18th century to the early 19th century, with the purpose of undertaking a set of structural reforms that would eliminate the obstacles that prevented economic and social development of the viceroyalty, and later, clearly, of the Republic of New Granada. This study was carried out from the perspective of the combination of methodological collectivism, in which material and cultural conditions are fundamental to contextualize and explain historical processes, and methodological individualism, which warns us of the presence and interference of individual episodes in the making of a process in time and space. This allowed us to establish that all the propositions presented in this brief period were born from the matrix of enlightened liberalism, since they proposed the liberation of the factors of production (land, capital and hand of work), the extinction of monopolies and the abolition of the of the indigenous tribute.